The mycetoma knowledge gap: identification of research priorities - Wanke, Bodo; Van de Sande, Wendy W. J.; Maghoub, El Sheikh; Fahal, Ahmed Hassan; Goodfellow, Michael; Welsh Lozano, Oliverio; Zijlstra, Ed E. (Public Library of Science, 2014)
Mycetoma is a tropical disease which is caused by a taxonomically diverse range of actinomycetes (actinomycetoma) and fungi (eumycetoma). The disease was only recently listed by the World Health Organization (WHO) as a neglected tropical disease (NTD). This recognition is the direct result of a meeting held in Geneva on February 1, 2013, in which experts on the disease from around the world met to identify the key research priorities needed to combat mycetoma. The areas that need to be addressed are highlighted here. The initial priority is to establish the incidence and prevalence of the disease in regions where mycetoma is endemic, prior to determining the primary reservoirs of the predominant causal agents and their mode of transmission to susceptible individuals in order to establish novel interventions that will reduce the impact of the disease on individuals, families, and communities. Critically, economical, reliable, and effective methods are required to achieve early diagnosis of infections and consequential improved therapeutic outcomes. Molecular techniques and serological assays were considered the most promising in the development of novel diagnostic tools to be used in endemic settings. Improved strategies for treating eumycetoma and actinomycetoma are also considered.